THE INFLUNCE OF BRAND COMMUNITY AND COMMUNITY ENGAGEMENT IN BUILDING BRAND TRUST: EMPIRICAL AT YESZY.MFG - Hafidh Rozziq Attaqi; Anton Agus Setyawan (FEBI UIN Sunan Gunung Djati Bandung, 2023)
A brand community is now not only a marketing tool for manufacturers but also a long-term business strategy to maintain the existence of a brand. The success of the brand community is shown through indicators of customer loyalty and also the willingness of customers to become brand advocates for brands promoted by the community. This study aims to determine the effect of brand community and community engagement in building brand trust at Yeszy.Mfg. This research method uses quantitative methods by taking samples using purposive sampling method, amounting to 100 respondents. Data analysis using SmartPls software. The results of this study state that there is an influence of brand community on brand trust, there is an influence of community engagement on brand trust, and community engagement is able to moderate community engagement on brand trust. Overall, the research findings emphasize the significance of brand community and community engagement in building brand trust within the Yeszy.Mfg brand community. By creating a supportive and engaging environment, the brand can enhance customer loyalty, advocacy, and long-term success.